Organic-rich, fine-grained contourites in an epicontinental basin: The Upper Jurassic-Lower Cretaceous Vaca Muerta Formation, Argentina - Paz, Maximiliano (2022)
Fil: Buatois, Luis. Department of Geological Sciences, University of Saskatchewan, Saskatoon, SK S7N 5E2, Canada